More Money for Health : Resource Mobilization for Universal Health Coverage in Armenia - Maduko, Franklin; Chukwuma, Adanna; Minasyan, Gevorg; Manookian, Armineh; Saldarriaga Noel, Miguel Angel; Tandon, Ajay (World Bank, Washington, DC, 2022)
Armenia has made significant gains in population health, but faces challenges in ensuring health care access, due to financial barriers. As mortality caused by infectious diseases has fallen over the past two decades, the prevalence of noncommunicable diseases (NCDs) has increased. The NCD burden can be reduced via public health measures, such as tobacco control exposure, and access to high-quality health care. However, financial barriers to access are a significant challenge.